Hyla vigilans Solano, 1971, a second species for the genus Scarthyla, redescription and distribution in Venezuela and Colombia - Barrio-Amorós, César L.; de Pascual, Amelia D.; Mueses-Cisneros, Jonh J.; Infante, Edwin; Chacón, Andrés (Zootaxa, 2006)
Hyla vigilans, a poorly known hylinae from Venezuela and Colombia, is redescribed and assigned to the genus Scarthyla based on external morphology and osteology. The call is analysed from localities from both sides of the Andes. When adult, Scarthyla vigilans is indistinguishable externally from S. goinorum; only calls and larvae distinguish the two species.